Travelogs of Journeys to Lithuania in Early 15th–19th Century: The Problem of Egodocumentality and Typology - Arvydas Pacevičius (Knygotyra)
The article discusses the egodocumentary travel writing of trips to/inside Lithuania, which is characterised by an autobiographical first-person narration, and examines its origins, development, and dissemination. Based on the methodological paradigms of research into the cultural heritage of a manuscript and printed book, the concepts of memory archive, book communication cycle, and the social life of books, an attempt is made to draw the boundaries among the types of this writing (typology), and the intentions of the writing and publishing process are revealed. The case study is based on manuscript and published travel descriptions by both Lithuanian and foreign authors for the routes in the territory of Lithuania or on the Lithuanian border. It was found that first-person narration and an author’s ‘participation’ are present not only in manuscript travel accounts that are personal and those belonging to one’s relatives (family, clan, descendants), but also in texts that engage a wider audience and are published and distributed through various media. The attempt at a typology of travel egodocumentation revealed a gap between a genetic taxonomy based on the notion of the personal archive as a treasure trove of memory and a literary classification based on contemporary genres of travel writing. Travel accounts were created on the basis of the worldview prevailing in the society of the Grand Duchy of Lithuania, which formed a canon different from the European one. Noteworthy are the hitherto understudied egodocumentary marginalia, diaries in calendars that reflect the culture of travel in the Grand Duchy of Lithuania.